Accumulating laser-coolable ions in a linear Paul trap for ultrahigh-density beam dynamics experiment. (November 2019) - Ito, K; Masuda, T; Higaki, H; Okamoto, H
Abstract: An ion plasma confined in a linear Paul trap (LPT) exhibits the dynamic behavior physically equivalent to that of a charged-particle beam in an alternating-gradient (AG) transport channel. The Simulator of Particle Orbit Dynamics (S-POD) is a compact apparatus designed on the basis of this fact for diverse beam-physics experiments. We have so far employed Ar + ions that can readily be produced from neutral Ar gas atoms through the electron bombardment process. A space-charge-induced tune shift of up to about 20% of the bare tune can be achieved in Ar + plasmas. We are now preparing for future S-POD experiment to explore even higher beam-density regions. For this purpose, a large number of Ca + ions need to be stored in the LPT. Since S-POD is equipped with a powerful laser cooler for Ca +, the use of this ion species vastly expands the density range we can survey. The production of an intense bunch of Ca + ions is, however, not so easy because of some technical reasons. By optimizing the operating condition of a multi-sectioned LPT, we succeeded in increasing the number of accumulated Ca + ions to the level comparable to Ar + ion plasmas. This paper reports on updated results of the experiment.